Formy podpory podnikání ve stavebnictví - Netušil, Ondřej (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Bakalářská práce řeší formy podpor pro malé a střední podnikání ve stavebnictví. Tyto podpory jsou především realizovány jako záruky pro firmu k získání úvěru u banky. Dále se zaměřuje na instituce, které tyto záruky realizují a hlídají, aby nebyly zneužity a byly vypláceny firmám, které dobře hospodaří a potřebují to. Praktická část v sobě zahrnuje analýzu jedné firmy z mého okolí a posouzení, zda by ji byla udělena jedna z vybraných záruk.

The intention of my finale bachelor work is to explain and solve different forms of grants for small and medium businesses within building industry. Those grants work as a guarantee for the business to get loans from the bank. Those businesses are obviously carefully pick by the institution. Those establishments have given criteria to avoid the misuse of those grants. The practical part of my work includes the breakdown of one local company and its chances to get the grant.
Forms of Enterprise Support in the Civil Engineering
Keywords: Drobné; malé a střední podnikání; operační program; záruka na bankovní úvěr; záruka za návrh do výběrového řízení; Ministerstvo průmyslu a obchodu; tiny business; small business and medium business; operating system; guaranteeing bank loans; guarantee for attendance at the interview; bord of trade and indusrty